Anthropometric approximation of body weight in unresponsive stroke patients. Issue 12 (10th May 2007) - Lorenz, M W; Graf, M; Henke, C; Hermans, M; Ziemann, U; Sitzer, M; Foerch, C
Abstract : Background and purpose: Thrombolysis of acute ischaemic stroke is based strictly on body weight to ensure efficacy and to prevent bleeding complications. Many candidate stroke patients are unable to communicate their body weight, and there is often neither the means nor the time to weigh the patient. Instead, weight is estimated visually by the attending physician, but this is known to be inaccurate. Methods: Based on a large general population sample of nearly 7000 subjects, we constructed approximation formulae for estimating body weight from simple anthropometric measurements (body height, and waist and hip circumference). These formulae were validated in a sample of 178 consecutive inpatients admitted to our stroke unit, and their accuracy was compared with the best visual estimation of two experienced physicians. Results: The simplest formula gave the most accurate approximation (mean absolute difference 3.1 (2.6) kg), which was considerably better than the best visual estimation (physician 1: 6.5 (5.2) kg; physician 2: 7.4 (5.7) kg). It reduced the proportion of weight approximations mismatched by >10% from 31.5% and 40.4% (physicians 1 and 2, respectively) to 6.2% (anthropometric approximation). Only the patient's own estimation was more accurate (mean absolute difference 2.7 (2.4) kg). Conclusions: By using an approximation formula based on simple anthropometric measurements (body height, and waist and hip circumference), it is possible to obtain a quick and accurate approximation of body weight. In situations where the exact weight of unresponsive patients cannot be ascertained quickly, we recommend using this approximation method rather than visual estimation.